Contribution of early nutrition on the development of malnutrition and allergic diseases in the first year of life: a study protocol for the Mother and Infant Cohort Study (MICOS) - Woon, Fui Chee; Chin, Yit Siew; Ismail, Intan Hakimah; Chan, Yoke Mun; Batterham, Marijka; Abdul Latiff, Amir Hamzah; Gan, Wan Ying; Appannah, Geeta (BioMed Central, 2018)
Background: Nutrition and environmental factors are essential for the education of the neonatal immune system. Epidemiological evidence has shown that malnutrition and allergic diseases that occur during early childhood share similar protective and risk factors. This paper describes the protocol of the Mother and Infant Cohort Study (MICOS), which aims to determine the contribution of early nutrition to the development of malnutrition and allergic diseases in infants’ first year of life. Methods: MICOS is a prospective cohort study conducted at selected government health clinics in two states, namely Selangor and Wilayah Persekutuan Kuala Lumpur, Malaysia. Women in their third trimester of pregnancy are recruited into the study and their infants will be followed-up at 3, 6, and 12 months of age. Information on prenatal factors including socio-demographic characteristics, obstetric history, pre-pregnancy body mass index, gestational weight gain, smoking, family history of allergic diseases, maternal dietary intake and sunlight exposure during pregnancy are obtained through face-to-face interviews. Postnatal factors including dietary intake, sun exposure, and anthropometric measurements of the mothers, as well as feeding practices, dietary intake, anthropometric measurements, and development of allergic diseases of the infants are assessed at each follow-up. Blood samples are collected from the mothers in the third trimester to determine 25-hydroxyvitamin D levels as well as from the infants at age 12 months to determine atopic sensitisation. Discussion: The concept of developmental origins of health and disease (DOHaD) which emphasises on the role of early life environments in shaping future health and disease susceptibility in adulthood has gained a huge interest in recent years. The DOHaD paradigm has influenced many fields of research including malnutrition and allergic diseases. While findings from the developed countries remain controversial, such studies are scarce in developing countries including Malaysia. The present study will determine the cause and effect relationship between early nutrition and the development of malnutrition and allergic diseases in infants’ first year of life.